ANALISIS KEKUATAN BUTT JOINT PENGELASAN SMAW PADA MATERIAL ST-37 DENGAN VARIASI ELEKTRODA DAN KECEPATAN PENGELASAN - Pamungkas, Deni; Hastuti, Sri; Taufik, Ikhwan (POLITALA PRESS, 2024)
Shield Metal Arc Welding (SMAW) welding in practice often faces challenges in the form of defects in the joints which damage the quality of the connection. One implementation of welding connections is the process of making a paddock. Poor welding can damage the paddock and harm its users. The research aims to determine the effect of welding speed and electrodes on the tensile strength, hardness and microstructure of ST-37 steel welded joints. The research used AWS E 7016 and AWS E 6013 electrodes with a current of 100 amperes and varying welding speeds of 0.2 cm/s, 0.3 cm/s and 0.4 cm/s. The highest tensile strength for the AWS E 7016 electrode was 460.32 MPa and the lowest for the AWS E 6013 electrode was 256.02 MPa. The highest hardness value on AWS E 7016 was 236.07 MPa and the lowest was on AWS E 6013, amounting to 176.86 MPa. The ferrite composition dominates the weld metal. Because ferrite is ductile and not too hard, it means that the weld metal area is ductile and the hardness is not too high.